Dioscin pretreatment ameliorates ferroptosis in cardiomyocytes after myocardial infarction via inhibiting endoplasmic reticulum stress - Chang Wu; Xueping Shen; Pan Lou; Dongyan Song (Molecular Medicine)
Abstract Background Myocardial infarction (MI) remains a leading cause of mortality globally, often resulting in irreversible damage to cardiomyocytes. Ferroptosis, a recently identified form of regulated cell death driven by iron-dependent lipid peroxidation, has emerged as a significant contributor to post-MI cardiac injury. The endoplasmic reticulum (ER) stress response has been implicated in exacerbating ferroptosis. Methods Here, we investigated the potential of Dioscin, a natural compound known for its diverse pharmacological properties, in mitigating ferroptosis in cardiomyocytes following MI by targeting ER stress. Results In animal models subjected to MI, administration of Dioscin notably improved cardiac function, reduced infarct size by approximately 24%, and prevented adverse remodeling, highlighting its therapeutic potential. Through in vitro and in vivo models of MI, we demonstrated that Dioscin treatment significantly attenuates ferroptosis in cardiomyocytes, as evidenced by a decrease in lipid peroxidation by about 19% and preserved mitochondrial integrity. Moreover, Dioscin exerted its protective effects by inhibiting ER stress markers, such as the phosphorylation levels of PERK and eIF2α proteins, and the expression levels of BIP and ATF4 proteins, thus disrupting the ER stress-mediated signaling cascade associated with ferroptosis. Conclusion Overall, our findings suggested that Dioscin holds promise as a therapeutic agent against post-MI cardiac injury by mitigating ferroptosis via the suppression of ER stress. Further investigations into the precise molecular mechanisms and clinical translation of Dioscin’s cardioprotective effects are warranted, offering a potential avenue for novel therapeutic interventions in MI-related cardiac complications. Graphical Abstract